Advances in multimedia modeling 19th International Conference, MMM 2013, Huangshan, China, January 7-9, 2013, proceedings, part I - International Conference, MMM 2013 ((Information systems and applications, incl. Internet/Web, and HCI, 2013)
The two-volume set LNCS 7732 and 7733 constitutes the thoroughly refereed proceedings of the 19th International Conference on Multimedia Modeling, MMM 2012, held in Huangshan, China, in January 2013. The 30 revised regular papers, 46 special session papers, 20 poster session papers, and 15 demo session papers, and 6 video browser showdown were carefully reviewed and selected from numeroues submissions. The two volumes contain papers presented in the topical sections on multimedia annotation I and II, interactive and mobile multimedia, classification, recognition and tracking I and II, ranking in search, multimedia representation, multimedia systems, poster papers, special session papers, demo session papers, and video browser showdown. Semi-supervised concept detection by learning the structure of similarity graphs.- Refining image annotation by integrating PLSA with random walk model.- Social media annotation and tagging based on folksonomy link prediction in a tripartite graph.- Can you see it? Two novel eye-tracking-basedmeasures for assigning tags to image regions.- visual analysis of tag co-occurrence on nouns and adjectives.- Verb-object concepts image classification via hierarchical nonnegative graph embedding.- Robust semantic video indexing by harvesting web images.- Interactive evaluation of video browsing tools.- Paint the city colorfully: location visualization from multiple themes.- Interactive video advertising: a multimodal affective approach.- GPS estimation from users’ photos.- Knowing who you are and who you know: harnessing social networks to identify people via mobile devices.- Hyperspectral image classification by using pixel spatial correlation.- Research on face recognition under images patches and variable lighting.- New network-based algorithm for human group activity recognition in videos.- Exploit spatial relationships among pixels for saliency region detection using topic model.- Mining people’s appearances to improve recognition in photo collections.- Person re-identification by local feature based on super pixel.- An effective tracking system for multiple object tracking in occlusion scenes.- Image search reranking with semi-supervised LPP and ranking SVM.- Co-ranking images and tags via random walks on a heterogeneous graph.- Social visual image ranking for web image search.- Fusion of audio-visual features and statistical property for commercial segmentation.- Learning affine robust binary codes based on locality preserving hash.- A novel segmentation-based video denoising method with boise level estimation.- Blocking artifact reduction in DIBR using an overcomplete 3D dictionary.- Efficient HEVC to H.264/AVC transcoding with Fntra mode decision.- SSIM-based end-to-end distortion model for error resilient video coding over packet-switched networks.- A novel and robust system for time recognition of the digital video clock using the domain knowledge.- On modeling 3-D video traffic.- A low-complexity quantization-domain H.264/SVC to H.264/AVC transcoder with medium-grain quality scalability.- Evaluation of product quantization for image search.- Rate-quantization and distortion-quantization models of dead-zone plus uniform threshold scalar quantizers for generalized Gaussian random variables.- Flexible presentation of videos based on affective content analysis.- Dynamic multi-video summarization of sensor-rich videos in geo-space.- Towards automatic music performance comparison with the multiple sequence alignment technique.- Multi-frame super resolution using refined exploration of extensive self-examples.-Iterative super-resolution for facial image by local and global regression.- Stripe model: an efficient method to detect multi-form stripe structures.- Saliency-based content-aware image mosaics.- Combining visual and textual systems within the context of user feedback.- A psychophysiological approach to the usability evaluation of a multi-view video browsing tool.- Film comic generation with eye tracking.- Quality assessment of user-generated video using camera motion.- Multiscaled cross-correlation dynamics on senseCam lifelogged images.- Choreographing amateur performers based on motion transfer between videos.- Large scale image retrieval with practical spatial weighting for bag-of-visual-words.- Music retrieval in joint emotion space using audio features and emotional tags -- Analyzing favorite behavior in flickr.- Unequally weighted video hashing for copy detection. refining image annotation by integrating PLSA with random walk model.- Social media annotation and tagging based on folksonomy link prediction in a tripartite graph.- Can you see it? Two e-tracking-basedmeasures for assigning tags to image regions.- Visual analysis of tag co-occurrence on nouns and adjectives.- Verb-object concepts image classification via hierarchical nonnegative graph embedding.- Robust semantic video indexing by harvesting web images.- Interactive evaluation of video browsing tools.- Paint the city colorfully: location visualization from multiple themes.- Interactive video advertising: a multimodal affective approach.- GPS estimation from users’ photos.- Knowing who you are and who you know: Harnessing social networks to identify people via mobile devices.- Hyperspectral image classification by using pixel spatial correlation.- Research on face recognition under images patches and variable lighting.- New network-based algorithm for human group activity recognition in videos.- Exploit spatial relationships among pixels for saliency region detection using topic model.- Mining people’s appearances to improve recognition in photo collections.- Person re-identification by local feature based on super pixel.- An effective tracking system for multiple object tracking in occlusion scenes.- Image search reranking with semi-supervised LPP and ranking SVM.- Co-ranking images and tags via random walks on a heterogeneous graph.- Social visual image ranking for web image search.- Fusion of audio-visual features and statistical property for commercial segmentation.- Learning affine robust binary codes based on locality preserving hash.- A novel segmentation-based video denoising method with noise level estimation.- Blocking artifact reduction in DIBR using an overcomplete 3D dictionary.- Efficient HEVC to H.264/AVC transcoding with fast intra mode decision.- SSIM-based end-to-end distortion model for error resilient video coding over packet-switched networks.- A novel and robust system for time recognition of the digital video clock using the domain knowledge.- On modeling 3-D video traffic.- A low-comple complexity ntization-Domain H.264/SVC to H.264/AVC transcoder with medium-grain quality scalability.- Evaluation of product quantization for image search.- Rate-quantization and distortion-quantization models of dead-zone plus uniform threshold scalar quantizers for generalized Gaussian Random variables.- Flexible presentation of videos based on affective content analysis.- Dynamic multi-video summarization of sensor-rich videos in geo-space.- Towards automatic music performance comparison with the multiple sequence alignment technique.- Multi-frame super resolution using refined exploration of extensive self-examples.-Iterative super-resolution for facial image by local and global regression.- Stripe model: an efficient method to detect multi-form stripe structures.- Saliency-based content-aware image mosaics.- Combining visual and textual systems within the context of user feedback.- A psychophysiological approach to the ssability evaluation of a multi-view video browsing tool.- Film comic generation with eye tracking.- Quality assessment of user-generated video using camera motion.- Multiscaled cross-correlation dynamics on senseCam lifelogged images.- Choreographing amateur performers based on motion transfer between videos.- Large scale image retrieval with practical spatial weighting for bag-of-visual-words.- Music retrieval in joint emotion space using audio features and emotional tags -- Analyzing favorite behavior in flickr.- Unequally weighted video hashing for copy detection.